Chapter 5.18 The Profession of Research Management and Administration in Aotearoa New Zealand - Heather Thomas (Emerald Publishing Limited, 2023)
Within Aotearoa New Zealand (NZ) research, funding is sourced from a wide range of NZ and international governments, industries, and philanthropic organisations. This chapter primarily focusses on NZ government public sector funding of research and innovation and the impact this has on research management and administration (RMA) in NZ. Along with an increase in the number and range of NZ organisations that compete for research funding, there has also been an increase in the complexity and range of roles that need to be undertaken by those involved in RMA. The Future Pathways green paper, released by the Ministry of Environment, Innovation & Employment in October 2021, has signalled a redesign of the `public' research system, which could lead to further changes in the roles and responsibilities of RMA.
10.1108/978-1-80382-701-820231052; 10.1108/978-1-80382-701-820231052; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262